Optimizing the anchoring structure for a super large cable-net structure with improved fatigue resistance. Issue 4 (March 2020) - Zhu, Wanxu; Sang, Runhui; Yang, Long; Lei, Huan
During its operation, the vast cable-net structure of China's Five-hundred-meter Aperture Spherical radio Telescope is subject to super high stress amplitude (up to 500 MPa) that the current anchoring structure is unable to bear. As a solution to this problem, this article presents an optimized anchoring structure that includes a main anchor cup and an auxiliary anchor cup. Typically used to compose Five-hundred-meter Aperture Spherical radio Telescope's cable-net structure, the S3-type cable is selected as the subject of analysis. In addition to anchoring limit and fatigue tests, a finite element analysis is conducted using the software ANSYS to set up a one-sixth three-dimensional high-precision numerical model to examine the contact–slip relationship between the steel wires and the chill casting. The following combination of structural parameters is found for an optimized design of the S3-type cable anchoring structure: auxiliary cup internal inclination angle, 3°; friction coefficient between anchor cup and chill casting, 0.12; and elastic modulus of the chill casting, 36 GPa. This optimal structural setting eliminates fretting wear in the main cup section; instead, fretting wear most likely occurs at the narrow end of the auxiliary anchor cup. When the structure bears the maximum working load, the slip amplitude between the chill casting and the tendons is 25 μm at the narrow end of the auxiliary anchor cup, and the radial compressive stress of the steel wire is −20 MPa. It is determined that this innovative anchoring structure with the S3-type cable boasts excellent static and dynamic load-bearing qualities with the elastic modulus of the cable remaining almost unchanged during the testing processes, which indicates that this anchorage meets the highly demanding requirements of the Five-hundred-meter Aperture Spherical radio Telescope project and offers a prototype to facilitate future anchoring enhancing efforts.